Progress on M1 Research. (9th February 2015) - Pietralla, N; Rainovski, G; Reese, M; Stahl, C; Beck, T; Beller, J; Romig, C; Werner, V
Abstract: Magnetic dipole transitions in nuclei can offer crucial information on nuclear structure, e.g., on spin-flip processes or on nuclear charge currents. Driven by the need for more comprehensive or more precise data on M 1 transitions in nuclei, we have recently tried to advance pre-existing experimental methods to meet the present needs. This contribution reports on the current status of our efforts on three aspects: (i) access of spin-flip M 1 strength in radioactive nuclei, (ii) quadrupole-collectivity of the M 1 scissors mode, and (iii) highest- precision measurements for strong ground-state M 1 excitations.